Ações educativas em programas de saneamento ambiental: estudo de caso em quatro municípios do Estado da Bahia, Brasil - Gonçalves, Lincoln de Souza (2009)
In Brazil, the Ministry of Health (MOH) has the National Health Foundation (FUNASA) as the executive body for the promotion of health and social inclusion by means of sanitation. Since 1999, the institution develops the Program of Health Educa-tion and Social Mobilization (PESMS) that integrates the public policy of the health sector. The program is aimed at the sustainability of actions, participation, mobilization and social control. The PESMS contains guidelines, theoretical foundations and meth-odologies that advocate critical processes and innovative practices. However, the pro-gram can be run with ambiguity, with misuse or to satisfy the condition of financial sup-port. The focus of research is to evaluate the Program for Health Education and Social Mobilization (PESMS) developed in four districts of the State of Bahia for implement-ing the sanitation systems funded by the National Health Foundation (FUNASA). The field research was diagnosed by means of case study, the actions with the health educa-tion program in the period 2001 to 2006. For research, the methodological techniques used were interviews (with people involved in the actions), direct observation (the inter-vention area) and information retrieval. The strategy was to compare the perceptions of the executors and beneficiaries in terms of the effectiveness of actions in sanitation and to verify the incorporation of the objectives of this for the community. The results indi-cate the lack of managers in relation to the educational goals and how to implement them in accordance with the guidelines of educational programs in health. Prevailing practice of the traditional education system based on lectures especially informative about the disease prevention and care of equipment. The participation and mobilization of the population limited to holding meetings. The analysis of past experiences provided subsidies for the improvement, implementation, planning and evaluation of future edu-cational activities to be developed by PESMS-FUNASA.